Roldán, M. Alganza and P. Papadopoulou (ed.). La mitología griega en la tradición literaria: de la Antigüedad a la Grecia contemporánea. Granada: Centro de Estudios Bizantinos, 2017. 444 p. ISBN 9788495905895 - Signes Codoñer, Juan (ΠΗΓΗ/FONS, 2019)
–